The Perception of Quality Nursing Work Environment among Hospital Nurses - Aric Vranada; Chiou-Fen Lin; Chia-Jung Hsieh; Tsae-Jyy Wang (International Journal of Nursing and Health Services (IJNHS), 2021)
Background: Nurses, the more significant health care provider, need an excellent work environment that adequately expresses their skills and knowledge on providing optimum care quality outcomes to the patients. Objective: This study aimed to determine the current state of the nurses’ perceived work environment quality and examine differences in perceived work environment quality among nurses with different characteristics. Method: A descriptive cross-sectional correlation design and a probability sampling method recruit 334 hospital nurses. The self-report questionnaire scale of the Quality Nursing Work Environment (QNWE) was used to collect data. Descriptive statistics, variant analysis (ANOVA), independent-sample t-test, and Pearson correlation were utilized to analyze comprehensive data. Result: The participants reported a perceived moderate level of quality of the work environment. The perceived QNWE levels were found to differ across participants' ages statistically (p<0.05), work experience (p<0.01), and department (p<0.05). Most participants rated their working environment as high quality on the domain "Professional specialization and cooperation" (M=2.81; SD=0.53). Contrarily, the responses to domain 2, "Staff quality," were ranked lower (M= 3.32; SD=0.63). Nurses who worked in the special care units and had three years or more experience perceived lower work environment quality than others did. Recommendation: The finding of this study can be utilized as a guideline to the policymakers, hospital administrators, nurse supervisors, and educators to determine areas to improve nurses' work environment; which could translate into a significant improvement in patient outcome